A triad of texts from fifth-century Southern China: the *Mahāmāyā-sūtra, the Guoqu xianzai yinguo jing, and a Mahāparinirvāṇa-sūtra Ascribed to Faxian - Radich, Michael (Journal of Chinese religions, 2018)
In previous work, I have shown that the (Mainstream, smaller) Mahāparinirvāṇa-sūtra ascribed to Faxian is in fact almost certainly not his work, and that internal evidence closely associates it with two other texts: the Guoqu xianzai yinguo jing ascribed to Guṇabhadra and the *Mahāmāyā-sūtra ascribed to Tanjing. This paper analyzes the content of these texts, in order to ascertain (as much as possible) their likely relation to one another; the context in which they were composed; and their relations to that context. In addressing questions of context, the analysis applies innovative computer-assisted methods, which allow us to pinpoint detailed clues of highly specific intertextual relationships among a broad range of texts. This enables us to discover in the present triad of texts internal evidence pointing to close relations to a very specific body of literature in the fifth century.